Existence of a solution in the Holder space for a nonlinear functional integral equation - Saha, Dipankar; Sen, Mausumi; Sarkar, Nimai; Saha, Subhankar (Armenian Journal of Mathematics, 2020)
This article is entirely devoted to the application of the measure of noncompactness defined in the Holder space. Here the emphasis is on the study of the nonlinear functional integral equation with changed arguments. Precisely, the existence of a solution is obtained by employing the Darbo fixed point theorem under certain hypotheses. Finally, we provide a tangible example which supports our results.